Structural elucidation of a pectic polysaccharide from Fructus Mori and its bioactivity on intestinal bacteria strains. (15th April 2018) - Li, Saijuan; Li, Meixia; Yue, Han; Zhou, Lishuang; Huang, Lulin; Du, Zhenyun; Ding, Kan
Highlights: The structure of a rhamnogalacturonan from Fructus Mori was characterized. The backbone of this polysaccharide was alternate 1, 4-α-Gal p A and 1, 2-α-Rha p . The branches contain T-, 1, 4- and 1, 3, 6-linked β-Gal p, T- and 1, 5-linked α-Ara f . This polysaccharide may promote growth of intestinal bacteria B. thetaiotaomicron . Abstract: Many studies suggested that polysaccharides could impact on the gut microbiota. To discover new polysaccharides which influence intestinal beneficial bacteria, a pectin polysaccharide FMP-6-S2 with an average molecular weight of 86.83 kDa was purified from Fructus Mori . The monosaccharide residue analysis indicated that FMP-6-S2 was composed of rhamnose, galacturonic acid, galactose and arabinose in a molar ratio of 30.86: 24.78: 28.70: 15.61. The backbone of FMP-6-S2 contained 1, 4-linked α-Gal p A and 1, 2-linked α-Rha p with branches substituted at C-4 position of rhamnose. The branches were composed of 1, 4-linked β-Gal p, terminal (T) − and 1, 3, 6-linked β-Gal p, T- and 1, 5-linked α-Ara f . Bioactivity test results suggested that FMP-6-S2 and its degraded product could promote growth of intestinal bacteria, B. thetaiotaomicron, which is a dominate strain in the gut of human to benefit intestinal mucosa. These results suggested that FMP-6-S2 and its degraded product might improve human wellness by modulating B. thetaiotaomicron .